1986
DOI: 10.1128/jb.166.3.779-786.1986
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the phospholipid precursor inositol and its relationship to growth and viability in the natural auxotroph Schizosaccharomyces pombe

Abstract: Phospholipid metabolism in the fission yeast Schizosaccharomyces pombe was examined. Three enzymes of phospholipid biosynthesis, cytidine diphosphate diacylglycerol synthase (CDP-DG), phosphatidylinositol (PI) synthase, and phosphatidylserine (PS) synthase, were characterized in extracts of S. pombe cells. Contrary to an earlier report, we were able to demonstrate that Cf)P-DG served as a precursor for PI and PS biosynthesis in S. pombe. S. pombe is naturally auxotrophic for the phospholipid precursor inositol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 36 publications
1
39
1
Order By: Relevance
“…Recent experiments have shown that the regulation of general phospholipid mnetabolism in S. pombe is considerably different from regulation in S. cerevisiae (12 (6,10). In contrast, the inositol-requiring yeast S. pombe exhibits a decrease in viability of less than 2 orders of magnitude after 120 h of inositol starvation (7). This increased resistance to inositol starvation may be due to several adaptations in S. pombe phospholipid metabolism.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Recent experiments have shown that the regulation of general phospholipid mnetabolism in S. pombe is considerably different from regulation in S. cerevisiae (12 (6,10). In contrast, the inositol-requiring yeast S. pombe exhibits a decrease in viability of less than 2 orders of magnitude after 120 h of inositol starvation (7). This increased resistance to inositol starvation may be due to several adaptations in S. pombe phospholipid metabolism.…”
Section: Discussionmentioning
confidence: 86%
“…This increased resistance to inositol starvation may be due to several adaptations in S. pombe phospholipid metabolism. These include a greater increase in the PS/PI ratio in response to inositol starvation and the ability of this organism to recycle inositol (7). A second difference between the two yeasts relates to phospholipid regulation in response to choline.…”
Section: Discussionmentioning
confidence: 99%
“…Drainas and their total fatty acid composition in S . pombe (White & Hawthorne, 1970;Johnston & Coddington, 1984;Fernadez et al, 1986). The present report gives detailed qualitative and quantitative data on the membrane phospholipids of S .…”
Section: Introductionmentioning
confidence: 99%
“…The membrane phospholipid composition of Schizosaccharomyces pombe is affected by the availability of phospholipid precursors (12,20). In particular, relative amounts of the major anionic phospholipids phosphatidylinositol (PI) and phosphatidylserine (PS) vary in response to the exogenous inositol concentration (12).…”
mentioning
confidence: 99%
“…
CDP-diacylglycerol (CDP-DG (12,20). In particular, relative amounts of the major anionic phospholipids phosphatidylinositol (PI) and phosphatidylserine (PS) vary in response to the exogenous inositol concentration (12).
…”
mentioning
confidence: 99%